Septic arthritis of the pubic symphysis: an atypical abdominal pain. Issue 1 (February 2015) - Ghislain, L.; Heylen, A.; Alexis, F.; Tintillier, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Septic arthritis of the pubic symphysis is a rare infection mostly caused by Staphylococcus aureus, and is traditionally associated with risk factors (sports, female incontinence surgery). Typical features of pubic symphysis infection include abdominal, pelvic, or groin pain that increases upon standing and walking, causing limping to occur. Acute onset of fever is often associated. It is important to distinguish septic arthritis of the pubic symphysis from its aseptic homologue, improperly called 'osteitis pubis' in English literature. This general term is mostly used to designate a mechanical pubic pain and has several aetiological meanings (joint stress, postoperative pain, rheumatic diseases). However, some authors consider the infection of the pubic symphysis as a variant of osteitis pubis, placing the two diseases in the continuum of the same entity. This confusion in pubic pathology related to its rarity and its atypical presentation, may in some cases lead to diagnostic and therapeutic delay. In this article, we would like to make practitioners aware of this uncommon and often ignored anatomical site, so that it can recover its place in the differential diagnosis of abdominal pain.